History of education : themes and perspectives - Raftery, Deirdre; Crook, David (London : Routledge, Taylor & Francis Group, 2014)
Specially commissioned to mark the 40th Anniversary of History of Education, and containing articles from leading international scholars, this is a unique and important volume. Over the past forty years, scholars working in the history of education have engaged with histories of religion, gender, science and culture, and have developed comparative research on areas such as education, race and class. This volume demonstrates the richness of such work, bringing together some of the leading international scholars writing in the field of history of education today, and providing readers with original and theoretically informed research. Each author draws on the wealth of material that has appeared in the leading SSCI-indexed journal History of Education, over the past forty years, providing readers with not only incisive studies of major themes, but delivering invaluable research bibliographies.
'This book was originally published as a special issue of History of Education.'--Page i.
Includes bibliographical references and index.
Keywords: Education -- History